Generalized Steffensen’s inequality by Lidstone interpolation and Montogomery’s identity - Fahad, Asfand (J Inequal Appl, 2018)
By using a Lidstone interpolation, Green’s function and Montogomery’s identity, we prove a new generalization of Steffensen’s inequality. Some related inequalities providing generalizations of certain results given in (J. Math. Inequal. 9(2):481–487, 2015) have also been obtained. Moreover, from these inequalities, we formulate linear functionals and describe their properties.